Sleep‐disordered breathing and cognitive functioning in preschool children with and without Down syndrome. Issue 8 (14th June 2017) - Joyce, A.; Dimitriou, D.
Abstract: Background: Sleep affects children's cognitive development, preparedness for school and future academic outcomes. People with Down syndrome (DS) are particularly at risk for sleep‐disordered breathing (SDB). To our knowledge, the association between SDB and cognition in preschoolers with DS is unknown. Methods: We assessed sleep by using cardiorespiratory polygraphy in 22 typically developing (TD) preschoolers and 22 with DS. Cognition was assessed by using the Mullen Scales of Early Learning and behaviour by using the Strengths and Difficulties Questionnaire (SDQ). The MacArthur Communicative Development Inventory (MCDI) measured language level. We predicted that sleep problems would be associated with lower cognitive and behavioural functioning. Results: In TD children, longer sleep duration was associated with higher scores on MCDI expressive language and fewer emotional symptoms such as fear and unhappiness on the SDQ, whilst SDB was associated with increased conduct problems and less prosocial behaviour on the SDQ. Conversely, for children with DS, SDB was associated with increased language understanding and use of actions and gestures on the MCDI. Conclusions: The findings in the TD group support our hypotheses. We recommend that sleep problems are screened for and treated as even mild SDB may prompt poorer cognition and behaviour. For children with DS, we expect that multiple factors in this complex syndrome mask or mediate the association between sleep and cognitive development and tighter controls are necessary to uncover effects of sleep. We propose longitudinal studies as a necessary tool to assess the precise impact of sleep on cognitive development in accounting for individual differences in DS.